Pengaruh Pemberian Responsible Terhadap Minat dan Hasil Belajar Siswa Villain Pada Pembelajaran Fisika Kelas Xi Ipa 1 Madrasah Aliyah Syekh Yusuf - Tahir, Fadliana; Ali, Mukti; Khuzaimah, Andi Ulfah (Al-Khazini: Jurnal Pendidikan Fisika, 2021)
This  study  aims  to  determine  whether  thegiving  of  responsible  affects  the  interest and  learning  outcomes  of  villain  students  in  learning  physics  class  XI  IPA  1 Madrasah Aliyah Syekh Yusuf. This type of research is a single-subject experimental research  using  the  A-B  design.  This  study  only  usesone  student  as  the  research subject,  and  students  who  are  the  subject  are  students  in  the  villain  category (naughty). Students who are classified as villains are obtained from the criteria listed in  several  instruments  used  such  as  interview  guidelines  and  sociometry  to  get subjects  with  the  villain  category.  Based   on  the  results  of  the  analysis   with descriptive  analysis  using  graphical  analysis,  the  average  percentage  of  interest  and learning  outcomes  for  the  baseline  phase  is  26.5%  and  59.9%.  Meanwhile, the average percentage of  interest and learning outcomes for the  intervention phase  was 92.5%  and  86.5%.  It  can  be  seen  that  the  average  in  the  baseline  phase,  namely  the conditions  that  have  not  implemented  the  treatment  in  the  form  of  providing responsibly  for  student  interest  and  learning  outcomes  is  very  low  compared  to  the intervention  phase,  namely  the  conditions  for  giving  responsibility.  So  it  can  be concluded  that  responsible  giving  affects  the  interest  and  learning  outcomes  of villain students